An integrated bayes soft switching interleaved and sliding window PWM for DC-DC boost converter - Puviarasi, R; Dhanasekaran, D (International Journal of Engineering and Technology, 2018)
In order to develop the efficient dc-dc boost converter in high output power application, an Integrated Bayes Interleaved and Sliding Window (IBI-SW) based PWM framework is proposed. Initially, the integration of interleaving and PWM improves the power factor correction in very high output power applications (photovoltaic panels) and near optimal voltage and current losses. Multiple phase shifts with soft switched Bayes interleaving technique maximizes the power generated in photovoltaic panels and the optimization of power conversion is achieved with sliding window based PWM that performs Maximum Power Point Tracking (MPPT) algorithm on the PV cells connected to the converter. The proposed dc-dc boost converter is efficiently tested on various load conditions for measuring the scalability of IBI-SW framework in multiple high power demanded application. When compared with traditional model, the simulation result of proposed IBI-SW based PWM framework demonstrates that the dc-dc converter improves the power generated in photovoltaic panels accurately and rapidly.Â Â